Mitochondrial Division Inhibitor 1 (mdivi-1) Protects Neurons against Excitotoxicity through the Modulation of Mitochondrial Function and Intracellular Ca2+ Signaling - Ruiz, Asier; Alberdi, Elena; Matute, Carlos (Frontiers in Molecular Neuroscience, 2018)
Excessive dynamin related protein 1 (Drp1)-triggered mitochondrial fission contributes to apoptosis under pathological conditions and therefore it has emerged as a promising therapeutic target. Mitochondrial inhibitor 1 (Mdivi-1) inhibits Drp1-dependent mitochondrial fission and is neuroprotective in several models of brain ischemia and neurodegeneration. However, mdivi-1 also modulates mitochondrial function and oxidative stress independently of Drp1, and consequently the mechanisms through which it protects against neuronal injury are more complex than previously foreseen. In this study, we have analyzed the effects of mdivi-1 on mitochondrial dynamics, Ca2+ signaling, mitochondrial bioenergetics and cell viability during neuronal excitotoxicity in vitro. Time-lapse fluorescence microscopy revealed that mdivi-1 blocked NMDA-induced mitochondrial fission but not that triggered by sustained AMPA receptor activation, showing that mdivi-1 inhibits excitotoxic mitochondrial fragmentation in a source specific manner. Similarly, mdivi-1 strongly reduced NMDA-triggered necrotic-like neuronal death and, to a lesser extent, AMPA-induced toxicity. Interestingly, neuroprotection provided by mdivi-1 against NMDA, but not AMPA, correlated with a reduction in cytosolic Ca2+ ([Ca2+]cyt) overload and calpain activation indicating additional cytoprotective mechanisms. Indeed, mdivi-1 depolarized mitochondrial membrane and depleted ER Ca2+ content, leading to attenuation of mitochondrial [Ca2+] increase and enhancement of the integrated stress response during NMDA receptor activation. Finally, lentiviral knockdown of Drp1 did not rescue NMDA-induced mitochondrial fission and toxicity, indicating that neuroprotective activity of mdivi-1 is Drp1-independent. Together, these results suggest that mdivi-1 induces a Drp1-independent protective phenotype that prevents predominantly NMDA receptor-mediated excitotoxicity through the modulation of mitochondrial function and intracellular Ca2+ signaling.